The Epidemiological and Microbiological Characteristics of the Postoperative Period in Older Patients in Cardiac Surgery - N. I. Gabrielyan; O. A. Savostyanova; E. M. Gorskaya; L. R. Batirchina; L. Yu. Romashkina; V. N. Poptsov; V. G. Akimkin (Эпидемиология и вакцинопрофилактика, 2015)
High-tech methods of surgical treatment of cardiac patients older than 65 years are the only means the ineffectiveness of drug treatments prolong their life and improve its quality. The analysis of the postoperative period of 5 years (2009 - 2013) cardiac patients older than 65 years compared with patients up to 65 years. The study used epidemiological and microbiological methods. The frequency of postoperative infectious complications was higher in patients older than 65 years In the structure of pathogens isolated from blood dominated negative bacteria: Acinetobacter spp., Klebsiella spp., Pseudomonas aeruginosa. There was a trend to a decrease in mortality in older patients in the dynamics over the years.